Normal flux distribution in 45o T-joint of three phase transformer core with staggered yoke and limb10mm - Ismail, Daut, Prof. Dr.; Ahmad, D. M. M. (ACTA Press, 2010)
Link to publisher's homepage at http://www.actapress.com/